A Comparison of Websites from Spanish, American and British Hospitals - Llinás, G.; Rodríguez-Iñesta, D.; Mira, J. J.; Lorenzo, S.; Aibar, C. (Methods of Information in Medicine, 2008)
Objective: To evaluate and compare the user-orientation of Spanish, American and British hospital websites.Methods: A descriptive study of 32 hospital portals (12 Spanish, 10 American and 10 British) was carried out in which the following were analyzed: website readability according to the Flesch Index, websites accessibility using the Web Accessibility Test, and the quality of information provided using the “e-Information Scale of Health Care Centers”.Results: Fifty percent of the user-oriented information quality attributes are met. Readability indices tend to be below 60 (standard readability), and only 10 of the 32 websites meet the accessibility criteria.Conclusions: Most portals exhibit accessibility problems that favor computer illiteracy. There is a wide variability in terms of website readability and in terms of useroriented content.
Keywords: Internet; hospital websites; quality; readability; accessibility